Sustainable and Responsible Investment: Concept and the Commonalities with Islamic Financial Institutions - Muhammad Zarunnaim bin Haji Wahab; Asmadi Mohamed Naim (ETIKONOMI, 2020)
This paper aims to highlight the Sustainable and Responsible Investment (SRI) concept, similarities, and opportunities with Islamic financial institutions (IFIs), especially in Malaysia's perspectives. This paper is conceptual., thus the methodology used in this paper is qualitative, focusing on document analysis method by analyzing previous literature, books, reports, official website, and articles. Based on the analysis, SRIs and IFIs share the same fundamental aim, which is to utilize the funds with high morals and ethics. Besides, the analysis also indicates that SRIs and IFIs have shown significant growth over the last two decades and became the most rapidly growing sectors. In the context of the opportunities, both concepts can become a new value proposition and product innovation in order to capture the future preferences of investors and customers. The IFIs and SRIs are capable of bridging the gap both entities considering their fundamental mutual aim, which is to utilize the funds through high morals and ethics.JEL Classification: E22, G20How to Cite:Wahab, M. Z. H., & Naim, A. M. (2020). Sustainable and Responsible Investment:Concept and the Commonalities with Islamic Financial Institutions. Etikonomi: Jurnal Ekonomi, 19(1), 141 – 154. https://doi.org/10.15408/etk.v19i1.13772.